E-EVENT INFORMATION SYSTEM AT ALUNG PRODUCTION BASED ON ANDROID - Arman Suryadi Karim; Eriyanda Adeta Pura (Proceeding International Conference on Information Technology and Business, 2018)
The development of technology in this modern era affects the majority of people to use Smartphone as a medium of communication in the daily life. Smartphone becomes a necessity in life, especially when people need to find information about an event and to book tickets at Alung Production. Consumers can immediately see information and book through Smartphone without coming to the location. The information system was based on minimum Android version by using Lolipop. The programming language used in this system was Java and the MySQL database. The method to develop this system used Waterfall with UML tools (use case diagrams, activitiy diagram, class diagramand Sequence diagrams). This information system contained the ticket booking service that facilitated consumers to register and to get the tickets about the event. There was the rating ranks to provide an assessment and comment on the information about the event. Therefore, it facilitated consumers to get information about events held by Alung Production.Keywords : Android, Java, MySQL, UML